The Effect of Financial Ratios and Macroeconomic Factors on Financial Distress in Technology Companies Listed on the Indonesia Stock Exchange - Khema Devi; I Nyoman Wijana Asmara Putra (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Financial distress refers to a condition where a company experiences financial difficulties and if it is not resolved immediately, it will lead to bankruptcy. Several models can be used to measure financial distress, one of which is the Zmijewski model. This study aims to analyze the influence of financial ratios and macroeconomic factors on financial distress among technology companies listed on the Indonesia Stock Exchange. The research was conducted at technology companies listed on the IDX for the 2020–2024 period, with a sample size of 44 companies selected using a purposive sampling method. The study employed secondary data derived from company financial statements obtained through the official IDX website and analyzed using SPSS version 27. The findings reveal that financial ratios specifically, profitability (ROE) have a significant negative effect on financial distress, while leverage (DER) has a significant positive effect. Meanwhile, macroeconomic factors such as inflation and interest rates have no effect on financial distress.